Manhaj Sarjana Hadith Dalam Menentukan 'Illah Dalam Periwayatan Al-Tafarrud: Kajian Perbandingan Antara Sarjana Mutaqaddimin Dan Muta'akhkhirin - Yaakob, M. A. bin; Shamsudin, R. (Universiti Sains Islam Malaysia, 2024)
There are differences in methods engaged by the mutaqaddimin as opposed to the muta’akhkhirin hadith scholars in deriving the ‘illah of the hadith narrations by way of al-tafarrud. This distinction can be seen through two main aspects, namely the method of determining the ‘illah and the terminology used to describe the existence of ‘illah in the narration of a hadith via tafarrud. Hence this article aims to examine both aspects that are contained in the methodologies employed by both the mutaqaddimin and the muta’akhkhirin hadith scholars in deriving ‘illah in tafarrud hadiths. In order to achieve these objectives, a qualitative study was conducted to procure the data through library research. The data was then analyzed based on inductive and deductive methods. The findings show that the mutaqaddimin hadith scholars determine ‘illah based on circumstantial evidence (qarinah) which shows there had been wahn in the concerned narration. The muta’akhkhirin hadith scholars on the other hand define ‘illah based on two main characteristics, namely the position of the narrators and the existence of the divergent textual-understanding element (al-mukhalafah) with other narrators.